Spatio-temporal Analysis and Health Risk Assessment of Particulate Matter (PM2.5) in Jalalabad City - Sadaat, Said Rahmatullah; Amn, Shahidullah; Hanifi, Spinghar (Journal of Natural Sciences – Kabul University, 2026)
Delicate particulate matter (PM2.5) is a serious threat to human health and the environment that requires continuous monitoring. This study was conducted to conduct a spatiotemporal analysis and health risk assessment of PM2.5 in Jalalabad city in 2024. PM2.5 was estimated based on MODIS Aerosol Optical Depth (AOD), spatial distribution was mapped using the Spline with Barriers method in ArcGIS; temporal changes were analyzed using Excel; and health risk assessment was performed using the Ostro formula. The results show that the PM2.5 level reached 279.287 µg/m³ in the central and industrial zones, well above the WHO and national standards. The results of the seasonal analysis show that the highest level was recorded in summer at 265.937 µg/m³. These findings indicate serious health risks and highlight the need for monitoring and management based on GIS and remote sensing.